Consumer preference for pork safety characteristics: Considering rational and irrational behavior. (June 2023) - Zhu, Dian; Tang, Yuhao; Wu, Linhai
Abstract: The food quality and safety incidents occurring continually in China are greatly sapping consumers' confidence in the food industry. Accordingly, this paper sets four characteristics (quality and safety, traceability information, traceability information authenticity certification, and price) with different levels of these characteristics for traceable pork as an example food product. The rational preferences and irrational characteristics of consumers were studied based on a survey of 636 consumers in Suzhou City, Jiangsu Province, China, using the hierarchical Bayesian estimation method and mixed Logit choice model. The results of the choice experiment (CE) based on the assumption of rational preferences indicated that Chinese consumers have the highest preferences for pork with a green certification mark, complete traceability information, and government-certified traceability information authenticity on the whole. In contrast, the findings of the irrational characteristics model built based on the CE showed that Chinese consumers have a higher degree of dependence on slaughtering and processing information than on complete traceability information, indicating that there may be differences in influence on consumer behaviors between consumers' rational preferences and irrational characteristics. The contributions of this paper are as follows: on the one hand, it tries to construct a suitable theoretical basis for irrational characteristics of consumers, and on the other hand, it can take the consumers' degree of dependence on safety characteristics as a point of penetration to improve food quality and safety in practice. Highlights: Construct a suitable theoretical basis for irrational characteristics of consumers. Consumers have the highest degree of dependence on slaughtering information. Rationality and irrationality have different effects on consumer choice.